2006
DOI: 10.1002/pi.1939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of filler‐to‐matrix blending ratio on the mechanical strength of palm‐based biocomposite boards

Abstract: The effect of the blending ratio of a polyurethane matrix and oil‐palm empty fruit bunch (EFB) fibers on the mechanical properties of biocomposite boards has been studied. The PU matrix and EFB fibers were used at blending ratios of 25:75, 30:70 and 35:65 (by weight). The mechanical property of hardness was studied. The intention of this study was to produce fiberboard from a vegetable oil‐based polyester as the matrix and biomass from the palm oil industry, namely EFB. It was found that the blending ratio wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
(27 reference statements)
1
15
0
3
Order By: Relevance
“…A similar trend was observed for natural rubber-oil palm fiber composites by Jacob et al 31 In another study, the water absorption of polyurethane-oil palm fiber composites increased sharply on the 1st day of immersion and remained constant for the next 5 days, and the composites with higher fiber contents absorbed more water. 30 For the same study, it was also reported that composites with 75% fiber content absorbed 55% water and composites with 65% fiber absorbed 48% water on the 1st day of immersion. In a similar study, it was found that coir fiber-low-density polyethylene/LLDPE composites absorbed 5.5% water at the end of 200 h of immersion in water at 25 C. 29 Alkali treatment of the fibers reduced the water absorption of the composites only at the higher fiber loadings of 40 and 50%.…”
Section: Water Absorptionmentioning
confidence: 81%
See 1 more Smart Citation
“…A similar trend was observed for natural rubber-oil palm fiber composites by Jacob et al 31 In another study, the water absorption of polyurethane-oil palm fiber composites increased sharply on the 1st day of immersion and remained constant for the next 5 days, and the composites with higher fiber contents absorbed more water. 30 For the same study, it was also reported that composites with 75% fiber content absorbed 55% water and composites with 65% fiber absorbed 48% water on the 1st day of immersion. In a similar study, it was found that coir fiber-low-density polyethylene/LLDPE composites absorbed 5.5% water at the end of 200 h of immersion in water at 25 C. 29 Alkali treatment of the fibers reduced the water absorption of the composites only at the higher fiber loadings of 40 and 50%.…”
Section: Water Absorptionmentioning
confidence: 81%
“…28,29 The high initial water absorption was contributed by the porous structure of the oil palm fiber, which transported the water via the capillaries in the fiber strands into gaps and flaws at the interfaces between the matrix and fibers. 30 The rate of water absorption of the oil palm fiber-LLDPE composites increased with fiber loading. The addition of more hydrophilic oil palm fiber caused a deviation from the hydrophobic nature of the composites, and such deviation was proportional to the amount of fiber added.…”
Section: Water Absorptionmentioning
confidence: 96%
“…Nesse sentido é necessário o desenvolvimento de novos produtos, como é o caso do estudo proposto por BRADI et al (2006), tendo avaliado a infl uência da mistura de óleo vegetal em matriz poliuretana na resistência mecânica de painéis de fi bras de madeira. As análises realizadas possibilitaram concluir que é possível a utilização de misturas de óleo vegetal em matriz poliuretana na relação de 35:65 (em massa) para confecção de painéis de fi bras de madeira.…”
Section: O Presente Trabalho Objetivou Avaliar As Características Físunclassified
“…Thus, the development of new products is necessary. As the study proposed by BRADI et al (2006). They evaluated the influence of mixture of vegetal oil in polyurethane matrix in mechanical strength of wood fiberboards.…”
Section: Introductionmentioning
confidence: 99%